Disciplinary Responsibility of the Government Employee in the Law of Saudi Arabia - Alshaikh, Hashem Baker (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the disciplinary responsibility of the public employee in the Saudi system. The research aims to identify the nature of disciplinary responsibility, and to identify its pillars of disciplinary responsibility in the Saudi law and system, and to identify the concept of the public employee in the Saudi legislation and system. It is governed by a general rule, as well as it relies on the comparative approach, which deals with a specific subject in two different systems, with the aim of presenting similarities and differences in order to clarify the disciplinary responsibility of the public employee in the Saudi system. The study reached the following most important results: 1.The disciplinary responsibility of the public employee is a principle recognized in the legal system according to the statutory texts and judicial rulings issued by the Disciplinary Authority and the Board of Grievances. This independence entails that the employee may be held disciplinary and criminal accountable for the same incidents, without prejudice to the rule that more than one penalty may not be imposed on the same act. 2.The disciplinary responsibility of the public employee does not preclude the dismissal of the employee from the public office if he is criminally convicted in one of the cases of dismissal by force of law, and the dismissal of the public employee in this case has arranged the maximum disciplinary penalties and by a decision of the competent administrative authority. 3.The disciplinary responsibility of the public employee is consistent with the need for the availability of the material and moral element and is distinguished from it by the necessity of the availability in addition to these elements of the capacity, which is the characteristic of the public employee, just as the presence of the willful element is not required for its establishment.